"Their place is beyond the town's border": A qualitative exploration of stigma associated with tuberculosis in rural and urban areas of Lagos, Nigeria. (25th January 2021) - Oladele, David A.; Idigbe, Ifeoma E.; Ekama, Sabdat O.; Gbajabiamila, Titilola; Ohihoin, Aigbe G.; David, Agatha N.; Ezechi, Oliver C.; Odunukwe, Nkiruka N.; Salako, Babatunde L.
Abstract: Tuberculosis (TB) remains a major public health challenge in Nigeria with a minimum yield of various TB control efforts due to sociocultural determinants of health including TB‐associated stigma. Therefore, to achieve the Sustainable Development Goal targets for TB control, an understanding and reduction in TB‐associated stigma is necessary. The study aims to explore the perspective of community members and investigate the possible ways of mitigating TB‐associated stigma in rural and urban areas in Lagos State, Nigeria. Eight focus group discussions (FGD) were conducted among eight homogenous groups of participants living in the community in rural and urban areas of Lagos state who were stratified by gender, between July and November 2017. Analysis of data was done using the modified grounded theory. A total of 86 participants took part in the FGDs. There were various stigmatising behaviours towards people infected with TB in rural and urban communities studied. This includes: Not willing to eat with people suffering from TB, withdrawal from TB patients in social gatherings, verbal abuse of TB patients and refusing to visit their houses because of their illness. There were also misconceptions about the cause of TB in our study which includes spiritual attack, ingestion of cat hair and inhalation of dust. However, participants in the study believed that mitigating the effect of TB‐associated stigma will require adequate community education on TB, provision of financial and emotional support to the patients, as well as the involvement of community leaders in TB control activities and stigma reduction interventions. TB‐associated stigma exists in rural and urban communities, with a lack of appropriate knowledge of TB and fear of infection as a major determinant in rural and urban areas respectively. Health education and sensitisation about TB, with community leaders as champions could help to mitigate the effect of TB‐associated stigma.